(untitled) (KASBIT Business Journal, 2020)
Microfinance is a disciplined and successful tool for Women empowerment and Self-employment. The microfinance Division in Pakistan has achieved significant progress and accomplished considerable cost creations. The key purpose of the research study is to examine the methods through which Microfinance increases women empowerment and the technique of self-employment in urban and rural areas of Sindh. The most central purpose of this study was to analyze the various effects of microfinance (MF) on women empowerment and Self-employment using financial liberalization theory. Scholar used Stratified random sampling technique, and 846 customers of ’Telenor Microfinance Bank” (TMB) and “Sindh Rural Support Organization” (SRSO) were selected for testing PLS through Smartpls 3. Furthermore, the evaluation of responses using PLS of measurement and structural model resulted in the demonstrations of an optimistic and significant impact on Dependent variables (DVs) by the independent variable (IV).